Correlations Between Acute Ischemic Stroke And Its Associated Cardiovascular Diseases - Daniela Arabadzhieva; Ara Kaprelyan; Zdravko Slavov; Zhaneta Georgieva; Aleksandra Tsukeva (Journal of Biomedical & Clinical Research)
The objective of this study was to analyze the association between some cardiovascular diseases and acute ischemic stroke. A total of 258 acute ischemic stroke patients (mean age 70.59±7.22 years) were examined. The presence of eight cardiovascular diseases and pathological conditions was analyzed: arterial hypertension, hypertensive heart, atrial fibrillation, myocardial infarction, ischemic heart disease, effort angina pectoris, coronary atherosclerosis, and heart failure. Data were statistically processed by variation and correlation analysis. Most male and female patients presented with four accompanying cardiovascular diseases (27 or 20.93% and 31 or 24.03% of the cases, respectively). There were two groups of four variables each - with a relatively strong and a moderate, as well as with a weak correlation (r